IMPLEMENTASI MODEL PEMBELAJARAN EXPLICIT INSTRUCTION UNTUK MENINGKATKAN PRESTASI BELAJAR MATA PELAJARAN MELAYANI MAKANAN DAN MINUMAN SISWA KELAS XI JASA BOGA 2 DI SMK WISATA INDONESIA - Yudhiet Fajar Dewantara (Program Studi Hospitality dan Pariwisata, 2020)
This study aims to find out how the application of Food and Beverage Learning with the application of explicit learning model learning in class XI Catering Services 2 and improve learning achievement of Serving Food and Beverages after using explicit instruction learning model. This research is a Class Action Research with research design starting with action planning, action implementation, observation, and reflection. This research was conducted at the Indonesian Vocational High School in August to September 2014. The subjects of this research were students of Wisata Indonesia Vocational School of Tourism majoring in Culinary Class XI Service Boga 2 2014/2015 academic year consisting of 35 students. Data collection techniques use documentation, observation, and learning outcome tests. The instrument used in this study is a test of learning outcomes. Data analysis techniques using quantitative descriptive analysis. The results of the study show that 1) The implementation of learning practices on the subject of serving food and drinks by applying Explicit Instruction learning method with two cycles. 2.) there is an increase in learning outcomes in the practice of presenting Food and Beverages class XI Cooking Class (TB) 1 in the breakfast sub-indicator settings table and sub-indicator structuring table for lunch for cycle II by applying Explicit Instruction method. This can be seen from the average value of the first cycle 67.83 for pre test I and 85.45 for post test I. While for cycle II is 75.90 for pre test II and 88.28 for post test II. If the percentage of student achievement increases, then the cycle I increases 67.5% and cycle II 75%. Based on this data all students at the end of the action can achieve the Minimum Completeness (KKM) standard.